“Prime Time Politics”: Popular Culture and Politicians in the UK - Street, John (Javnost-The Public, 2000)
Politicians and parties are making increase use of popular culture. They make use of its practitioners, its generic conventions, its image and much else. This association with popular culture has provoked much derision, and the suggestion that democracy is being damaged in the process. This article contributes to this debate by illustrating the way in which politics and popular culture have become linked, and by exploring the reasons for this linkage. It then goes on to examine this relationship through two case studies, both drawn from the British Labour Party, which allows to examine in more detail how politics communicates through popular culture. Rather than seeing politics. use of popular culture as either a welcome populism or a dumbing down, the article argues that we need to look more closely and critically at the texts themselves, judging them aesthetically as well as culturally.